Genome-wide association analysis uncovers novel rice blast resistance alleles - Greenwood, Julian; Lacorte-Apostol, Vanica; Kroj, Thomas; Padilla, Jonas; Telebano-Yanoria, Mary; Glaus, Anna; Roulin, Anne; Padilla, Andre; Zhou, Bo; Keller, Beat; Krattinger, Simon (Research Square Platform LLC, 2023)
One of the most critical steps following genome-wide association studies (GWAS) is the identification and validation of candidate genes underlying genetic associations. Gene presence-absence and copy number variations can significantly hamper candidate gene discovery if high-quality genomic resources from specific crop cultivars are unavailable. This is particularly true for disease resistance genes, which are often located in highly dynamic genomic regions. Here, we perform a genome-wide association analysis of rice blast resistance in 500 genetically diverse rice accessions. To facilitate candidate gene identification, we produced de-novo genome assemblies of ten rice accessions that showed rice blast resistance associations. These assemblies facilitated the identification and validation of novel alleles of the rice blast resistance genes Ptr and Pia. Our work shows that GWAS in combination with whole-genome sequencing are powerful tools for gene cloning and uncovers an allelic series for the unusual Ptr rice blast resistance gene.